Game Modding as an Informal Source of Brands in Virtual Worlds of Computer Games - Magdalena Hofman-Kohlmeyer (Communications of International Proceedings, 2021)
A Number of researches confirmed influence ON product placement in computer games on brand reception but still lacks knowledge about brand introduction by players through game modding. In June 2020, the author carried out an online survey amongst computer game players (N=1157). The survey was aimed AT investigating game modding as an informal source of brands in computer games. The author tried to evaluate the scale of  producing branded mods by players. A online survey result showed that 53% of players created or downloaded a mod and 69,2% of them created or downloaded a branded modification. Players also indicated best remembered brands form the game and 28,2% of them were introduce into game by modding community. Moreover, adding the brand to the virtual product made this product more attractive than if it were anonymous for 67,1% of players.
Keywords: Brands; Computer Games; Game Modding; User-Generated Content; Value Co-Creation.